Agrarian cooperativism strategies facing recent social and productive transformations: An exploration in South west Buenos Aires (Argentina) - Lopez Castro, Natalia (Cooperativismo & Desarrollo, 2020)
Objective: This article analyzes the way in which agricultural cooperatives of two parts of the southwest of the Buenos Aires province —Púán and Adolfo Alsina— faced the context of recurrent crises and general decline, which was registered in the last decades in the entire region of the Pampas. Methodology: With a qualitative methodological approach, the various strategies used by the associative entities between 2002 and 2017 to achieve their permanence and consolidation in the territories are studied; the factors that were significant in its delineation and future prospects. Results: The specificities of the experiences and their points in common with what happened in similar entities in other areas of the region are indicated. Conclusions: The analyzed strategies allow us to reflect on the tensions that arise between the consolidation of a concentrated productive economic model and the proposals of the social economy; and, on the enabling conditions for the possibility of rethinking the social organization of production and territories in more diverse and democratic terms.